Polymerization of ε-Caprolactone Using a Ruthenium(II) Mixed Metallocene Catalyst - Mendes, Paulo J. (2017)
Aliphatic polyesters, prepared by ring opening polymerization (ROP) of lactones, are versatile polymers with good mechanical properties, hydrolyzability, biocompatibility and biodegradabil- ity that make them quite suitable for medical and environmental applications. The objective of this work is the ROP of ε-caprolactone via the activated monomer mecha- nism (using isopropyl alcohol as an initiator and a ruthenium(ii) mixed metallocene catalyst).This polymerization is quantitative and occurs in a controlled manner, yielding a product with a dispersity (Đ) in the range 1.1–1.3. The ruthenium catalyst is exceptionally stable under the experimental conditions and can be recovered at the end of the reaction.